Surface electromyography of the foot: A protocol for sensor placement - Branthwaite, Helen; Aitkins, Christopher; Lindley, Steven; Chockalingam, Nachiappan (Foot (Edinburgh, Scotland), 2019)
•A protocol for sEMG placement is defined for intrinsic foot muscles.•Four of six intrinsic muscles showed good correlation for the validity of the protocol.•Flexor hallucis Brevis and Abductor Hallucis muscles did not show good validity.•Improved protocols and technology of EMG of the intrinsic foot muscles are required. The use of surface EMG (sEMG) to record muscle activity is common place yet due to restrictions in technology studies on the intrinsic foot muscles have been limited or only fine wire instruments have been used. This paper looks at the potential reliability of a sEMG protocol for assessing the intrinsic foot muscles. Six intrinsic muscles were defined using ultrasound and muscle function testing. A protocol for sensor placement was created with repeatability and reliability testing of the protocol conducted by three separate testers on three subjects over two different time frames. Inter tester and Inter session repeatability and reliability was measured with ICC and percentage standard error of measurement. Although there was good correlation between Extensor Digitorum Brevis, Dorsal Interossei, Abductor Digiti Minimi and Flexor Digitorum Brevis there was increased variability and poor correlation for Flexor hallucis Brevis and Abductor Hallucis. The percentage standard error of measurement did not support the high ICC values indicating a lower precision of measurement. Variability between testers and sessions shows an inconsistent reliability of sEMG and further work is required with protocols focussing on grouping muscles to improve the understanding of the intrinsic foot muscles.